2019
DOI: 10.32479/irmm.8771
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Intention to Use Netflix: An Extended Technology Acceptance Model Approach

Abstract: Developments in information and communication technologies disrupt the traditional media ecosystem. New media has led to the emergence of many digital platforms such as Netflix. Netflix has become very popular nowadays all over the world. Hence, this paper aims to reveal the determinants of intention to use Netflix based on the technology acceptance model. For this purpose, a survey of 251 respondents in Istanbul was conducted. The findings indicate that (i) self-efficacy and knowledge is positively related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
(38 reference statements)
4
14
0
Order By: Relevance
“…There is an effect of PEOU on knowledge (RO4-H3a). This result reflects those of Cebeci et al (2019) in their research on understanding the intention to use Netflix, who also found that knowledge is related to both PEOU and PU. They are consistent with previous research (Bailey et al, 2017;Kim et al, 2010;Liu & Tai, 2016;Sá nchez-Prieto et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There is an effect of PEOU on knowledge (RO4-H3a). This result reflects those of Cebeci et al (2019) in their research on understanding the intention to use Netflix, who also found that knowledge is related to both PEOU and PU. They are consistent with previous research (Bailey et al, 2017;Kim et al, 2010;Liu & Tai, 2016;Sá nchez-Prieto et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Mac Callum and Jeffrey (2013), who also found the study indicated that ICT (information and communications technology) abilities directly correlate with intentions to utilise mobile learning. Cebeci et al (2019) in their research on understanding the intention to use Netflix, found that knowledge is related to both PEOU and PU. Bailey et al (2017); Kim et al (2010); Liu and Tai (2016); Sá nchez-Prieto et al (2017) also found that knowledge is related to both PEOU and PU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This analysis is aligned with other published research on students' satisfaction with online teaching-learning models. Some of the earlier efforts also applied TAM models [15,16,35,39,45,46]. Others were validated through alternative organizational models, such as relational coordination [8,9,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the moderating effect of technology anxiety in the technology adoption domain has not been explored much. Cebeci et al (2019) reported that technology anxiety attenuates the positive effect of perceived usefulness on the attitude toward "Netflix"one of the global online streaming service retailers. Lin and Chang (2011) examined the moderating effect of technology readiness on the relationships between perceived usefulness, perceived ease of use, attitude and behavioral intention toward SSTs.…”
Section: Moderating Role Of Personality Traitsmentioning
confidence: 99%